2021
DOI: 10.3390/pharmaceutics13020217
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring New Long-Lasting Intravitreal Formulation for Glaucoma with Vitreous Images Using Optical Coherence Tomography

Abstract: Intravitreal injection is the gold standard therapeutic option for posterior segment pathologies, and long-lasting release is necessary to avoid reinjections. There is no effective intravitreal treatment for glaucoma or other optic neuropathies in daily practice, nor is there a non-invasive method to monitor drug levels in the vitreous. Here we show that a glaucoma treatment combining a hypotensive and neuroprotective intravitreal formulation (IF) of brimonidine–Laponite (BRI/LAP) can be monitored non-invasive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 42 publications
(90 reference statements)
4
11
0
Order By: Relevance
“…The left eyes from both models also showed a slight increase in cell number (Figure 7). The results of these two in-depth analyses are in agreement with previous results for relative VIT/EPR intensity [49].…”
Section: Quantification Of the Mean Number Of Opacities/cellssupporting
confidence: 91%
See 3 more Smart Citations
“…The left eyes from both models also showed a slight increase in cell number (Figure 7). The results of these two in-depth analyses are in agreement with previous results for relative VIT/EPR intensity [49].…”
Section: Quantification Of the Mean Number Of Opacities/cellssupporting
confidence: 91%
“…This technique was validated in subsequent studies [ 46 , 78 ]. Rodrigo et al [ 49 ] described greater vitreous signal in rats with glaucoma than in healthy rats. Recently, a study performed in humans using OCT identified ramified macrophage-like cells on the retinal surface, suggesting a hyalocyte origin (but without histological confirmation), with altered morphology in patients with retinopathies and associated with areas of retinal nerve fibre layer (RNFL) thinning in glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The retina posterior pole, retinal nerve fiber layer (RNFL), and ganglion cell layer (GCL) protocols were used. 39 41 , 43 , 44 All of them measured a 3-mm-diameter area centered on the optic disc using 61 b-scans, and subsequent follow-up examinations were performed at this same location using eye-tracking software and a follow-up application. The retina posterior pole protocol analyzed the thickness from the inner limiting membrane to the retinal pigment epithelium divided into the 9 Early Treatment Diabetic Retinopathy areas, 45 which included a central 1-mm circle centered on the optic disc (no fovea exists in rats), and inner (inferior, superior, nasal, temporal) and outer (inferior, superior, nasal, temporal) rings measuring 2 and 3 mm in diameter, respectively, as well as total volume; the RNFL protocol analyzed the thickness from the inner limiting membrane to the GCL boundaries divided into 6 sectors (inferotemporal, inferonasal, superotemporal, superonasal, nasal, and temporal); and the GCL protocol analyzed from the RNFL to the inner nuclear layer boundaries within the Early Treatment Diabetic Retinopathy areas.…”
Section: Methodsmentioning
confidence: 99%